(untitled) (Community Based Medical Journal, 2026)
The emergence of antimicrobial resistance necessitates the search for novel antibacterial agents. Saffron (Crocus sativus L.) petals, a major by-product of saffron production, are a potential source of bioactive compounds. This experimental study in the Department of Pharmacology and Therapeutics in collaboration with the Department of Microbiology, Mymensingh Medical College, Bangladesh, between July 2022 and June 2023, to evaluate in vitro antibacterial activity of saffron petal extracts against common pathogenic bacteria. Aqueous (ASE) and methanolic (MSE) extracts of saffron petals were prepared. Their antibacterial activity against standard strains of Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Pseudomonas aeruginosa (P. aeruginosa) was assessed using the disc diffusion method to determine the zone of inhibition (ZOI) and the broth dilution method to determine the minimum inhibitory concentration (MIC). Both extracts exhibited concentration-dependent antibacterial activity. The methanolic extract (MSE) demonstrated superior potency. The largest ZOI (24 mm) was observed against S. aureus at 500 mg/ml for both extracts. The MIC values for MSE were 50 mg/ml for S. aureus and 250 mg/ml for both E. coli and P. aeruginosa. The MIC values for ASE were 100 mg/ml for S. aureus and E. coli, and 250 mg/ml for P. aeruginosa. S. aureus was the most susceptible organism. The positive control, Gentamicin, showed significantly lower MICs (0.75-1 µg/ml), as expected. subculture studies confirmed the bactericidal action at the determined MICs. Saffron petal extracts, particularly the methanolic fraction, possess significant in vitro antibacterial activity. These findings validate the traditional use of this agricultural waste and position saffron petals as a promising, sustainable source for further investigation into novel antimicrobial agents. CBMJ 2026 July: Vol. 15 No. 02 P:106-113